Factors Associated With Failed Focal Neocortical Epilepsy Surgery. Issue 6 (29th August 2014) - Englot, Dario J.; Raygor, Kunal P.; Molinaro, Annette M.; Garcia, Paul A.; Knowlton, Robert C.; Auguste, Kurtis I.; Chang, Edward F.
Abstract: Background: Seizure outcomes after focal neocortical epilepsy (FNE) surgery are less favorable than after temporal lobectomy, and the reasons for surgical failure are incompletely understood. Few groups have performed an in-depth examination of seizure recurrences to identify possible reasons for failure. Objective: To elucidate factors contributing to FNE surgery failures. Methods: We reviewed resections for drug-resistant FNE performed at our institution between 1998 and 2011. We performed a quantitative analysis of seizure outcome predictors and a detailed qualitative review of failed surgical cases. Results: Of 138 resections in 125 FNE patients, 91 (66%) resulted in freedom from disabling seizures (Engel I outcome). Mean ± SEM patient age was 20.0 ± 1.2 years; mean follow-up was 3.8 years (range, 1–17 years); and 57% of patients were male. Less favorable (Engel II–IV) seizure outcome was predicted by higher preoperative seizure frequency (odds ratio = 0.85; 95% confidence interval, 0.78–0.93), a history of generalized tonic-clonic seizures (odds ratio = 0.42; 95% confidence interval, 0.18–0.97), and normal magnetic resonance imaging (odds ratio = 0.30; 95% confidence interval, 0.09–1.02). Among 36 surgical failures examined, 26 (72%) were related to extent of resection, with residual epileptic focus at the resection margins, whereas 10 (28%) involved location of resection, with an additional epileptogenic zone distant from the resection. Of 16 patients who received reoperation after seizure recurrence, 10 (63%) achieved seizure freedom. Conclusion: Insufficient extent of resection is the most common reason for recurrent seizures after FNE surgery, although some patients harbor a remote epileptic focus. Many patients with incomplete seizure control are candidates for reoperation.